Quantitative measurements of haemophilic joint tissues by point‐of‐care musculoskeletal ultrasound: Associations with clinical and functional joint outcome parameters. Issue 5 (25th June 2021) - Mesleh Shayeb, Akram; Barnes, Richard F.W.; Hanacek, Cris; Aguero, Peter; Steiner, Bruno; Bailey, Cindy; Quon, Doris; Kruse‐Jarres, Rebecca; von Drygalski, Annette
Abstract: Background: Painful arthropathy is a long‐term complication in patients with hemophilia (PWH), affecting mobility and quality of life. A major barrier for the appraisal of joint health is the absence of point‐of‐care (POC) imaging modalities to promptly identify and manage arthropathic changes. Accordingly, we developed the Joint tissue Activity and Damage Exam (JADE) POC musculoskeletal ultrasound (MSKUS) protocol. JADE is validated for haemophilic joint tissue recognition with high intra/inter‐rater and inter‐operator reliability. Aims: Evaluate associations of JADE with clinical (Hemophilia Joint Health Score, [HJHS]) and functional (total arc [combined flexion and extension range of motion [ROM]]) parameters. Methodology: In this multi‐centre prospective study, we recruited PWH A or B with at least one arthropathic joint. We evaluated joint health (both elbows, knees, and ankles) by comparing JADE measurements (soft tissue and cartilage thickness, and osteochondral alterations) with HJHS and total arc. Results: Of 44 PWH, most had hemophilia A (35/44), were severe (36/44) and had a median age of 36 years. Increasing HJHSs and declining total arc, indicating worsening arthropathy, were associated with JADE measurements in the expected direction, including (1) increasing length of osteochondral alterations, (2) diminished cartilage thickness, and (3) greater soft tissue expansion. The ankles had the highest proportion of joints without measurable (missing) cartilage. In multivariable models MSKUS measurements explained 68% and 71% of the variation in HJHS and total arc respectively for the elbow, 55% and 29% respectively for the knee, and 50% and 73% for the ankle. Conclusions: This study highlights the associations of direct intra‐articular ultrasonography measurements using the JADE protocol with clinical and functional parameters. Our findings underscore the clinical value of POC MSKUS using the JADE protocol as a complementary instrument for the diagnosis and management of haemophilic arthropathy.